Analisis Pengendalian Risiko Keselamatan dan Kesehatan Kerja (K3) dengan Metode Failure Mode and Effect Analysis (FMEA) pada PT. ABC (Universitas Muhammadiyah Yogyakarta, 2023)
PT. ABC is engaged in metal casting such as drinking water pipe connections and quality drainage components. Existing manufacturing processes involve direct interaction of workers with equipment in production situations that have sufficiently high safety risks. The research aims to identify the type or source of hazard, determine the value of high risk, and appropriate risk control measures. Using the Failure Mode and Effect Analysis (FMEA) method to identify failures from facilities, systems or equipment that have an impact on work accidents. The results of the study found 48 hazards with identifying the risk of work accidents with categories are very low (7), low (48), medium (17), high (10) and there is no risk of work accidents with very high categories. Work accidents that have a high risk in the metal casting process at PT. ABC is at the die-making, smelting and pouring, roughing, and finishing work stations. Potential risks to work safety include dust from mixing, being crushed by solid iron, exposed to sparks, exposed to molten liquids, electrocuted, and exposed to odors from paint. Risk control measures are proposed in the metal casting process at PT. ABC is carried out with engineering control and the use of PPE according to the source of danger.